Students’ Algebraic Thinking Ability Based on Gender - Iskandar, Iskandar (Hayati : Jurnal Pendidikan, 2026)
Algebraic thinking plays a fundamental role in developing students’ mathematical reasoning, particularly in recognizing patterns, representing relationships, and generalizing mathematical ideas. This study aims to describe students’ algebraic thinking abilities based on gender and to determine whether there is a significant difference between male and female students. The research employed a descriptive comparative method involving eighth-grade students as the sample, selected using total sampling. Data were collected through a written test designed to measure key components of algebraic thinking, including generational, transformational, and meta-global abilities. The data were analyzed using descriptive statistics (percentage, mean, and standard deviation) and inferential statistics through the Mann–Whitney U test. The results indicate that male students’ algebraic thinking ability is categorized as moderate, with an average score of 51.48, while female students demonstrate a higher level of ability categorized as good, with an average score of 61.53 (as shown in the results table on page 5). Female students outperform male students across all components of algebraic thinking, particularly in transformational abilities. Statistical analysis reveals a significant difference between the two groups (p < 0.05), indicating that gender influences students’ algebraic thinking performance. The findings suggest that female students tend to be more accurate, systematic, and careful in solving algebraic problems, while male students are more likely to rely on arithmetic or intuitive approaches. This study highlights the importance of designing instructional strategies that support the development of algebraic thinking for all students while considering gender differences. Further research is recommended to explore effective teaching approaches that enhance students’ algebraic thinking skills comprehensively.